Formation of hydrophobic polymer coatings on the track-etched membrane surface. Issue 1 (June 2021) - Kravets, L I; Yarmolenko, M A; Gainutdinov, R V; Satulu, V; Mitu, B; Dinescu, G
Abstract: Methods of forming coatings on the hydrophilic poly(ethylene terephthalate) track-etched membrane surface by means of plasma polymerization of organic compounds, magnetron sputtering and electron-beam dispersion of polymers in vacuum are considered. It is shown that the usage of compounds with low surface energy as pristine materials to coatings application allows to obtaining hydrophobic coatings on the membrane surface. The resulting composite membranes with hydrophilic and hydrophobic layers can be used in membrane distillation processes for desalination of seawater.